Implementasi Awig-Awig Terhadap Krama Tamiu dan Tamiu dalam Hukum Adat Bali - Dewi, Ni Made Liana; Chandra Satriana, I Made Wahyu; Karyasa, I Nyoman (Universitas Negeri Malang, 2024)
This study aims to analyze the implementation and inhibiting factors in the implementation of awig-awig towards krama tamiu and tamiu. This study uses descriptive empirical legal research methods. Awig-awig in the Pedungan Traditional Village has been applied to krama tamiu and tamiu. The application of awig-awig to krama tamiu and tamiu is contained in Pawos 6 Awig-Awig of Pedungan Traditional Village which explains the recognition of krama tamiu and tamiu as part of the traditional village population which must comply with all applicable regulations. Inhibiting factors in the implementation of awig-awig towards krama tamiu and tamiu include the low level of understanding of krama tamiu and tamiu towards traditional village awig-awig, lack of socialization of awig-awig to the community, as well as village officials' lack of understanding of awig-awig which causes discrepancies in the implementation of village regulations.